2009
DOI: 10.1186/1744-859x-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation and the family burden in schizophrenia: a randomized controlled trial

Abstract: BackgroundThe majority of patients with schizophrenia live with their relatives in Pakistan, thereby families experience a considerable burden. We aimed to study the impact of psychoeducation on the burden of schizophrenia on the family in a randomised controlled trial.MethodsA total of 108 patients with schizophrenia and their family members from the outpatient department of a teaching hospital in Lahore, Pakistan were randomised. Both groups received psychotropic drugs but one group received psychoeducation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 20 publications
3
42
0
11
Order By: Relevance
“…Entre os métodos/técnicas pedagógicas utilizados ao longo do programa, presume-se que as discussões orientadas e os trabalhos de grupo foram os mais eficazes, por serem os que melhor proporcionaram a possibilidade dos participantes esclarecerem as suas fortes", ambas respeitantes à Dimensão "Avaliação global das sessões". dúvidas, partilharem as suas ideias e preocupações com o formador e com o grupo (Baptista, 2007;Brewer, 1997), que se trata de uma das necessidades sentidas pelos familiares de doentes com esquizofrenia (Caqueo-Urízar et al, 2014;Chan et al, 2009;Nasr & Kausar, 2009).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Entre os métodos/técnicas pedagógicas utilizados ao longo do programa, presume-se que as discussões orientadas e os trabalhos de grupo foram os mais eficazes, por serem os que melhor proporcionaram a possibilidade dos participantes esclarecerem as suas fortes", ambas respeitantes à Dimensão "Avaliação global das sessões". dúvidas, partilharem as suas ideias e preocupações com o formador e com o grupo (Baptista, 2007;Brewer, 1997), que se trata de uma das necessidades sentidas pelos familiares de doentes com esquizofrenia (Caqueo-Urízar et al, 2014;Chan et al, 2009;Nasr & Kausar, 2009).…”
Section: Resultsunclassified
“…Este parecer encontra-se subjacente nas seguintes afirmações: P8-"Foi útil porque trocamos ideias e partilhámos experiências passadas no dia-a-dia" e P9-"(…)gostei muito aprendemos muitas coisas ouvindo os outros". Estes resultados vêm ao encontro de vários estudos que defendem que uma das potencialidades dos programas de psicoeducação, é serem realizados em grupo promovendo a interação e partilha de experiências entre indivíduos que têm problemas da mesma índole (Bechdolf et al, 2010;Chan et al, 2009;Nasr & Kausar, 2009) O programa ANCORAGEM, também apresentou algumas limitações que importa referir para melhorar edições futuras. Entre, as limitações apontadas ao programa, foram destacadas: a falta de tempo para explorar mais cada um dos tópicos e os períodos de discussão e de esclarecimento de dúvidas, por vezes, centrarem-se e alongar-se nas reflexões e questões colocadas por alguns dos participantes.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…It may indicate inadequate health education (including mental health) that is often associated with poor health promoting activity [49]. On the other hand, the burden can be reduced with improved knowledge about illness and treatment [50].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown a relationship between caring for a schizophrenic relative and burden (Raj et al, 1991;Biegel et al, 1994;Martens and Addington, 2001). More recently Nasr and Kausar (2009) found that a family psycho-educational intervention significantly reduced caregiver's levels of burden in Pakistan. On the contrary Gonzalez-Blanch et al (2010) found no effect from a brief family intervention on either burden or EE in Spain.…”
Section: Introductionmentioning
confidence: 99%